Pola Hidup Bertoleransi : Analisis Konstruksi Sosial Masyarakat Desa Cisantana, Kabupaten Kuningan - Agung Nugraha, Satrio; Masrukin; Puspitasari, Elis (Kajian Moral dan Kewarganegaraan, 2025)
Tolerance in Cisantana Village is not a natural phenomenon, but rather the result of a complex social construction involving externalization, objectification, and internalization, as explained by Peter L. Berger and Thomas Luckmann's theory. This study aims to analyze patterns of tolerant living as a form of social construction, identify the factors that shape and maintain practices of tolerance, and understand the community's interpretation of tolerance in Cisantana Village. A descriptive qualitative research method was used to explore and understand the tolerance constructed by the community of Cisantana Village in their daily lives, with a primary focus on data collection through literature review. The results of the study show that the externalization of tolerance in Cisantana Village is evident in everyday actions, such as the simultaneous sounding of the azan and church bells without disruption, and interfaith participation in the Seren Taun traditional ceremony. Even in times of grief, residents of various faiths pray according to their respective religious teachings, demonstrating the internalization of the spirit of inclusivity through social practices. Objectification occurs when tolerance practices become institutionalized social norms, evidenced by the presence of places of worship from various religions without discrimination, as well as the acceptance of households with different beliefs as a matter of course. Informal policies from community leaders and the village government that grant religious freedom, supported by the local culture of mutual cooperation, further legitimize the value of tolerance, making it widely accepted and passed down across generations. Internalization is reflected in individuals who accept the social reality of tolerance as part of their self-awareness. Children in Cisantana Village grow up with harmonious interfaith interactions, viewing differences as normal and not forming exclusive groups based on religion. Social symbols, such as religious attributes coexisting in celebrations, further reinforce the collective awareness that all religions teach goodness and that differences are part of divine plan. Thus, tolerance in Cisantana Village is the product of organized subjective dynamics, shaping an objective social reality that is passed down through generations..